Polylactic acid: Characteristics, properties and applications in technique fields and biomedicine - Chinh, Nguyen Thuy; Hoang, Thai (Vietnam Journal of Science and Technology, 2022)
Polylactic acid (PLA) is one of the common aliphatic polyesters synthesized from lactic acid monomer (2-hydroxyl propionic acid) by fermentation or chemical synthesis. Due to its high strength, high modulus, biodegradability, compostability and well-known safety profile, PLA becomes a very useful material for both fundamental researches and practical applications. However, awareness of PLA manufacturing knowledge combined with understanding of its physico-chemical properties is essential for fruitful applications of PLA. This review article presents the synthesis, characteristics, properties and applications in technique and biomedicine fields of PLA. Among them, main synthesis methods of PLA will be mentioned. The physical, mechanical, thermal, gas permeable, electrical, and chemical properties of PLA will be described. The applications of PLA in packaging materials, agriculture, or other technique fields and biomedicine also help readers have a better overview of PLA.